Pengaruh Promosi Dan Citra Merek Terhadap Keputusan Pembelian Air Minum Dalam Kemasan (AMDK) Club Di Kecamatan Singaparna - Devi Roatul Padilah; Isyana Rahayu (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
This study aims to understand and analyze how promotions and brand image influence the purchase of Club bottled water in the Singaparna subdistrict. The research employed a quantitative approach using a survey methodology. To select the sample, the researcher used non-probability sampling with a purposive sampling method. In this study, the sample consisted of 96 respondents who were residents of Singaparna Subdistrict who had previously purchased or used Club BBD. Data analysis was conducted using the Partial Least Squares (PLS) approach with SmartPLS software. The findings indicate that promotions have a positive and significant impact on purchasing decisions, with a t-statistic value of 2.343 and a significance level of 0.019. Additionally, brand image also has a positive and significant impact on purchasing decisions, with a t-statistic of 6.576 and a significance level of 0.000. This study demonstrates that the better the promotions and brand image of AMDK Club, the more consumers decide to make a purchase. Therefore, the company must improve its promotional strategies and maintain its brand image to enhance consumers’ purchasing decisions.